Breaking boundaries: Exploring gendered challenges and advancing equality for Iranian women careers in tourism - Carrasco-Santos MJ; Seyfi S; Hosseini S; Hall CM; Mohajer B; Almeida-García F; Cortes Macías R (Elsevier Ltd, 2024)
While there's growing interest in gender and employment issues in tourism studies, a gap exists when examining the obstacles women face in career pursuits, especially in theocratic societies. Drawing on Risman's gender structure theory, this qualitative study investigates how Iranian women perceive the impact of gender power dynamics on their careers and those of their peers. The findings reveal inhibitory factors affecting women's quest for equal career opportunities, including deeply ingrained societal influences on gender roles, institutionalized gender discrimination, and self-imposed constraints. The findings also demonstrate how gender stereotypes and theocratic structures manifest in the Iranian tourism industry, and how Iranian women working in the tourism sector actively negotiate, resist, and challenge these stereotypes to advance their careers. In a field where most gender-related studies originate from Western perspectives, this study holds particular significance in amplifying the voices of those in non-Western, theocratic societies.
Keywords: Gender inequality; Gender power dynamics; Gender stereotypes; Career obstacles; Women empowerment; Iranian women